DESIGN OF FILE ENCRYPTION AND DECRYPTION APPLICATION USING AES-256 CRYPTOGRAPHY ALGORITHM BASED ON STREAMLIT - Rosandi, Arditya Adjie; Supriyono, Dhicky Hariyadi; Aulia, Teguh Tegar; Asri, Jefry Sunupurwa (International Journal of Multidisciplinary Research and Literature, 2026)
The widespread use of personal computing devices has led to an increasing number of sensitive documents, including digital files, lacking adequate cryptographic protection, raising the risk of data leakage and misuse. The Advanced Encryption Standard (AES) with a 256-bit key length is a symmetric-key cryptographic algorithm recommended for protecting data confidentiality due to its strong security and excellent performance. This study designs and implements a simple web-based application for file encryption and decryption using the AES-256 algorithm with a password-based key, built on the Streamlit framework. Key generation uses PBKDF2-HMAC-SHA256 with a random salt and a sufficient number of iterations, while data encryption uses AES-GCM, which provides confidentiality and integrity authentication. The application enables users to upload files, encrypt them into .enc ciphertext files, and restore them to their original form via a web interface, eliminating the need for direct command-line interaction. Experiments using several test files of varying sizes to assess the success of the encryption/decryption processes and estimate processing times. Furthermore, to ensure that data could not be accessed without the correct key, negative tests were conducted using erroneous passwords. All test files can be successfully encrypted and decrypted; encrypted files cannot be read directly; and the overhead of encryption and decryption is manageable for everyday use. The prototype app is a suitable solution to enhance the security of local file storage.